An organic white coating material with ultraviolet radiation resistance and low solar spectrum absorptivity and a preparation method thereof
By combining rare earth oxides with ZnO and using ALD technology to design the thermal control coating, the problem of performance degradation of existing thermal control coatings under ultraviolet radiation is solved, and a high-performance thermal control coating that is resistant to ultraviolet radiation is achieved, improving the thermal control coating The thermal control performance and reliability of the spacecraft.
Patent Information
- Application Number
- CN202410684817.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-05-30
AI Technical Summary
The existing thermally controlled coatings are affected by solar ultraviolet radiation in the space environment, resulting in degradation of optical performance and affecting the spacecraft's on-orbit reliability and life.
By compositeing rare earth oxides with ZnO and designing composite materials using ALD technology, the composition and structure of pigments are accurately controlled, and a high-performance thermally controlled coating that is resistant to ultraviolet radiation is prepared.
The performance of thermal control coating under ultraviolet radiation is achieved, and the durability and reliability of spacecraft thermal control materials are improved.
Smart Images

Figure CN118440547B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of spacecraft thermal control materials, and specifically relates to an organic white coating material with ultraviolet radiation resistance and low solar spectrum absorption rate and a preparation method thereof, which has very important application value. Background Art
[0002] In the space environment, due to direct sunlight, spacecraft need to withstand extreme temperature changes. The thermal control system is one of the important guarantee systems for the normal operation of spacecraft, and it needs to function all the time during the on-orbit operation. A large amount of thermal control materials are required in the spacecraft thermal control system to keep the spacecraft temperature within the normal range and ensure the stable use of the spacecraft during the sensitive period. Among the thermal control materials, pigment-based thermal control coatings have become the most widely used type of thermal control materials in spacecraft due to their cost-effectiveness, large-area construction, and construction on various curved and complex-shaped surfaces. The surface thermal equilibrium temperature of the spacecraft can be adjusted through its own thermophysical properties, namely the solar absorption ratio and hemispherical emissivity.
[0003] Paint-type thermal control coatings are mainly composed of pigments and binders. The pigments reduce the surface temperature of the coating by reflecting VIS and NIR as well as their own thermal radiation, thus playing a role in thermal control. In paint-type thermal control coatings, the most common pigments are metal oxides or metal salts such as ZnO, ZrO2, and BaSO4; binders are used to bond, fix, and disperse pigments, playing a role in maintaining the stability of the performance of the thermal control coating. Paint-type thermal control coatings can often be divided into inorganic thermal control coatings and organic thermal control coatings according to the type of binder. Inorganic thermal control coatings often use solutions such as potassium silicate, phosphate, and titanate as binders, while organic thermal control coatings often use epoxy resins, acrylic resins, and silicone resins as binders. Compared with inorganic thermal control coatings, organic thermal control coatings have good optical properties, excellent flexibility, and good adhesion to the substrate, and have become the focus of research in the field of thermal control coatings. However, the combined effects of solar electromagnetic rays, charged particles, atomic oxygen and other space environments during the on-orbit service of thermal control coatings will lead to degradation of optical performance, directly affecting the on-orbit reliability and life of spacecraft. For organic thermal control coatings, the ultraviolet radiation effect in solar electromagnetic rays is particularly significant. Although the solar ultraviolet radiation energy accounts for only a small proportion of the total solar radiation energy, the ultraviolet photon energy is very high, which is enough to break the chemical bonds with lower binding energy such as CC, CO, CN in organic polymers, thereby destroying the internal structure of the material, causing the color to deepen, and in severe cases even causing surface cracking or peeling, resulting in a decrease in the performance of polymer materials, thereby leading to the degradation of thermal control performance. Therefore, it is particularly important to develop an organic white coating that is resistant to ultraviolet radiation and has low solar spectrum absorption.
[0004] In order to prevent the destructive effect of ultraviolet radiation on organic adhesives, a common strategy is to select pigments that can absorb ultraviolet light and reduce the intensity of ultraviolet radiation on organic adhesives, thereby effectively reducing the damage of ultraviolet radiation to the adhesive in the thermal control coating and improving the stability of the coating under the action of the space environment. ZnO is a wide-bandgap II-IV compound semiconductor with a bandgap width of 3.37eV at room temperature. When it is exposed to ultraviolet radiation, the electrons in the valence band absorb the energy in the ultraviolet light and cross the bandgap to reach the conduction band. At this time, holes are generated in the valence band due to electron transition. The electrons that have transitioned to the conduction band are unstable and easily recombine with the holes in the valence band. When they recombine, they release energy in the form of light or heat without chemical reaction, which is equivalent to converting the absorbed ultraviolet rays into other forms of energy, thereby reducing the damage of ultraviolet radiation to organic adhesives. However, the ability of ZnO electron transition is limited.
[0005] The use of rare earth oxides as thermal control coating materials is rarely mentioned in existing technologies and materials, and there is little research on the development and utilization of new materials.
[0006] Traditional thermal control materials often only consider the ultraviolet absorption of zinc oxide pigment powder, but ignore the combination with other materials to improve the ultraviolet absorption performance of pigment powder. The design of traditional thermal control materials is single.
[0007] In addition, some researchers have studied the modification methods of composite materials, but the general methods have problems such as high requirements for sample preparation and modification conditions, and cannot maintain the stability of material properties, and have limitations in application. Summary of the invention
[0008] Compared with the singleness of traditional thermal control material design, the present invention compounds rare earth element oxides with ZnO and utilizes the special electronic structure of rare earth oxides to regulate the electronic transition behavior of ZnO, thereby achieving stable performance of the thermal control coating under ultraviolet radiation.
[0009] The present invention adopts ALD technology to design ZnO-based composite materials in a targeted manner. Due to the unique advantages of ALD technology, the thickness of film growth is accurately controlled by controlling process conditions to obtain nanometer or even sub-nanometer ultra-thin films or quantum dots. The present invention selects ALD technology to deposit rare earth oxides on ZnO powder, which can accurately control the composition and structure of the pigment and prepare a high-performance ultraviolet radiation-resistant thermal control coating. Accurately controlling the material composition and structural morphology of the composite material, maintaining the stability of the process, and ensuring the stability of the material in performance greatly improves the possibility of its practical application.
[0010] The present invention deposits rare earth oxides on ZnO materials by ALD technology, and further modifies ZnO to enhance the ability of ZnO electron transition. After the present invention uses rare earth elements to modify ZnO, the number of ZnO electron-hole pairs can be increased, and the protection ability of ZnO to organic binders can be improved. The present invention uses ALD technology to deposit rare earth oxides on ZnO powder, which can accurately control the composition and structure of the pigment and prepare a high-performance ultraviolet radiation-resistant thermal control coating. As a thermal control coating resistant to ultraviolet radiation, it is of great significance for the material development in the field of thermal control material technology for spacecraft.
[0011] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0012] The object of the present invention is to provide a method for preparing an organic white coating material that is resistant to ultraviolet radiation and has low solar spectrum absorption rate. The method first uses ALD technology to modify the surface of ZnO powder to prepare Y2O3@ZnO, CeO2@ZnO, La2O3@ZnO powder materials, and then mixes the rare earth oxide modified powder material (Y2O3@ZnO, CeO2@ZnO or La2O3@ZnO powder material) with an organic binder to evenly prepare a white slurry. Finally, the white slurry is sprayed on an alloy substrate by spraying technology. After drying, an organic white coating with low solar spectrum absorption rate and resistant to ultraviolet radiation is formed on the alloy substrate.
[0013] Further defined, the surface modification of ZnO powder by ALD technology is directly transferred to the reaction chamber for coating and modification. The temperature of the reaction chamber is set, the partial pressure of the precursor H2O and the rare earth element source precursor of the rare earth oxide is set, and pulses are alternately introduced into the chamber, and high-purity nitrogen (volume purity is 99.999%) is used to purge the residual gas between pulses. Deposition is carried out according to the set parameters, and after the deposition is completed, the modified powder is taken out.
[0014] It is further defined that the rare earth element source precursors corresponding to the rare earth oxides Y2O3, CeO2, and La2O3 are yttrium acetoamidinate, methylcyclopentadienyllanthanum, and cyclopentadienylcerium, respectively.
[0015] It is further defined that the flow rate of the inert fluidizing gas (high-purity nitrogen (volume purity is 99.999%)) is 40 ml / min-120 ml / min, for example 40 ml / min, 60 ml / min, 80 ml / min, 100 ml / min, 120 ml / min, etc.
[0016] Further defined, the temperature in the cavity can be 200°C-300°C, for example, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, etc.
[0017] It is further defined that the pulse time of the rare earth element source precursor of the rare earth oxide can be 5s-25s, for example 5s, 10s, 15s, 20s, 25s, etc.
[0018] Further limiting, the pulse time of the oxygen source precursor of the rare earth oxide can be 5s-25s, for example 5s, 10s, 15s, 20s, 25s, etc.
[0019] It is further defined that the purge gas cleaning time during the deposition process can be 10s-30s, for example 10s, 15s, 20s, 25s, 30s, etc.
[0020] Further limiting, the number of deposition cycles can be 100 cycles-300 cycles, for example 100 cycles, 150 cycles, 200 cycles, 250 cycles, 300 cycles, etc.
[0021] It is further defined that the modified pigment (such as Y2O3@ZnO, CeO2@ZnO, La2O3@ZnO powder material) and the organic binder are uniformly mixed using a cutting mixer to obtain a white slurry.
[0022] It is further defined that the organic adhesive is selected from epoxy resin, acrylic resin, silicone, and polyethylene;
[0023] It is further defined that the pigment-to-base ratio (i.e., the mass ratio of the white slurry to the organic binder) is (1:1)-(1:5), such as 1:1, 1:2, 1:3, 1:4, 1:5, etc.;
[0024] Further defined, the stirring rate is 1000-3000 rpm, such as 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, etc.;
[0025] It is further defined that the stirring time is 1-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.
[0026] It is further defined that the metal substrate is selected from aluminum alloy, titanium alloy, magnesium alloy, etc.;
[0027] It is further defined that the spraying distance is 10-30 cm, for example 10 cm, 15 cm, 20 cm, 25 cm, 30 cm;
[0028] It is further defined that the spraying pressure is 0.4-1 MPa, for example 0.4 MPa, 0.6 MPa, 0.8 MPa, 1 MPa.
[0029] The present invention also provides a coating prepared by any of the above methods.
[0030] The present invention utilizes ALD technology to perform surface modification on ZnO powder to prepare rare earth oxide modified ZnO powder material, the rare earth oxide modified ZnO powder material is uniformly mixed with resin to form white slurry, and finally the slurry is sprayed on an alloy substrate by spraying technology, and after drying, an organic white coating with low solar spectrum absorption rate and UV resistance is formed on the alloy substrate, and the composition and surface morphology of the coating material can be controlled by adjusting the process conditions of ALD deposition, the pigment-to-base ratio of the slurry and the process conditions of spraying.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention utilizes rare earth element oxides and ZnO for the first time to form a composite. On the one hand, rare earth elements have a high refractive index, an extinction coefficient close to zero, and good ultraviolet reflection ability. On the other hand, rare earth elements have a special electronic structure, which can regulate the electronic transition behavior of ZnO, so that ZnO absorbs ultraviolet energy and releases it in the form of electron-hole recombination, reducing the damage to the organic adhesive, thereby achieving stable performance of the thermal control coating under ultraviolet radiation.
[0033] The present invention uses ALD technology to deposit rare earth oxides on ZnO powder, which has certain technical difficulties, and specifically designs the pigment powder of the paint-type thermal control coating. By regulating the ALD deposition process conditions, the material composition and structural morphology of the composite material can be accurately controlled to prepare a high-performance thermal control coating. The modification uniformity of the ALD process ensures the stability of the material performance, greatly improving the possibility of its practical application.
[0034] The coating of the present invention has different loading states of rare earth oxide-modified ZnO, so the content and morphology of rare earth oxide in the rare earth oxide-modified ZnO can be designed according to different ultraviolet radiation intensities. The rare earth oxide and ZnO cooperate with each other, so that the white organic coating has excellent durability against ultraviolet radiation.
[0035] In addition, the white coating of the present invention has a low solar absorption ratio and a high emissivity, and has stable structural performance and excellent mechanical properties under extreme conditions (pressure, temperature, and irradiation). It is suitable for the actual mission environment of spacecraft and can be used in fields such as deep space exploration.
[0036] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1This is the XPS graph of the Y2O3@ZnO-200cycle pigment powder prepared in Example 1 of the present invention;
[0038] Figure 2 The solar spectrum absorption test results of the Y2O3@ZnO-200cycle white coating prepared in Example 1 of the present invention;
[0039] Figure 3 This is the spectral emission test result of the Y2O3@ZnO-200cycle white coating prepared in Example 1 of the present invention;
[0040] Figure 4 These are the test results of the Y2O3@ZnO-200cyclee white coating prepared in Example 1 of the present invention before and after ultraviolet irradiation. DETAILED DESCRIPTION
[0041] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, and do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all belong to the present invention.
[0042] Example 1: The preparation method of the Y2O3@ZnO-200cycle-A coating in this example is carried out by the following steps:
[0043] Step 1. Preparation of Y2O3@ZnO-200cycle modified powder is as follows:
[0044] Directly transfer ZnO powder to the reaction chamber for coating and modification. Set the temperature of the reaction chamber to 250°C, the partial pressure of the precursor H2O and yttrium acetamidine to 5Pa, alternately pass into the chamber in pulse form, the source pulse time is 20s, and high-purity nitrogen (volume purity is 99.999%) is used to purge the residual gas between pulses. The gas flow rate is 80ml / min, and the ALD cycle is set to 200cycles. According to the above parameter settings, after the deposition is completed, take out the modified powder.
[0045] Step 2. Prepare white slurry:
[0046] Acrylic resin was selected as the organic binder, the pigment-to-base ratio was set to 1:3, the speed of the cutting mixer was set to 2000 rpm, and the mixture was stirred at room temperature for 2 h to obtain a white slurry.
[0047] Step 3. Spray the white slurry obtained in step 2 onto the alloy substrate:
[0048] Aluminum alloy was selected as the metal substrate. The aluminum alloy substrate after sandblasting was ultrasonically cleaned with acetone and anhydrous ethanol, and placed in the spraying room after drying. The spraying distance was controlled to be 20 cm, the spraying pressure was 0.6 MPa, and after the spraying thickness reached 200 μm, it was dried in an oven at 80°C for 2 hours to obtain an organic white coating with low solar spectrum absorption rate that was resistant to ultraviolet radiation.
[0049] Example 2: The preparation method of the Y2O3@ZnO-250cycle coating in this example is carried out by the following steps:
[0050] Step 1. Preparation of Y2O3@ZnO-200cycle modified powder is as follows:
[0051] Directly transfer ZnO powder to the reaction chamber for coating and modification. Set the temperature of the reaction chamber to 250°C, the partial pressure of the precursor H2O and yttrium acetamidine to 5Pa, and alternately pass them into the chamber in pulse form. The source pulse time is 20s. Use high-purity nitrogen (99.999% volume purity) to purge the residual gas between pulses. The gas flow rate is 80ml / min, and the ALD cycle is set to 250cycles. After the deposition is completed according to the above parameter settings, take out the modified powder.
[0052] Step 2. Prepare white slurry:
[0053] Acrylic resin was selected as the organic binder, the pigment-to-base ratio was set to 1:3, the speed of the cutting mixer was set to 2000 rpm, and the mixture was stirred at room temperature for 2 h to obtain a white slurry.
[0054] Step 3. Spray the white slurry obtained in step 2 onto the alloy substrate:
[0055] Aluminum alloy was selected as the metal substrate. The aluminum alloy substrate after sandblasting was ultrasonically cleaned with acetone and anhydrous ethanol, and placed in the spraying room after drying. The spraying distance was controlled to be 20 cm, the spraying pressure was 0.6 MPa, and after the spraying thickness reached 200 μm, it was dried in an oven at 80°C for 2 hours to obtain an organic white coating with low solar spectrum absorption rate that was resistant to ultraviolet radiation.
[0056] Example 3: The preparation method of the Y2O3@ZnO-200cycle-B coating in this example is carried out by the following steps:
[0057] Step 1. Preparation of Y2O3@ZnO-200cycle modified powder is as follows:
[0058] Directly transfer ZnO powder to the reaction chamber for coating and modification. Set the temperature of the reaction chamber to 250°C, the partial pressure of the precursor H2O and yttrium acetamidine to 5Pa, and alternately pass them into the chamber in pulse form. The source pulse time is 20s. Use high-purity nitrogen (99.999% volume purity) to purge the residual gas between pulses. The gas flow rate is 80ml / min, and the ALD cycle is set to 200 cycles. According to the above parameter settings, after the deposition is completed, take out the modified powder.
[0059] Step 2. Prepare white slurry:
[0060] Acrylic resin was selected as the organic binder, the pigment-to-base ratio was set to 1:2, the speed of the cutting mixer was set to 3000 rpm, and the mixture was stirred at room temperature for 2 h to obtain a white slurry.
[0061] Step 3. Spray the white slurry obtained in step 2 onto the alloy substrate:
[0062] Aluminum alloy was selected as the metal substrate. The aluminum alloy substrate after sandblasting was ultrasonically cleaned with acetone and anhydrous ethanol, and placed in the spraying room after drying. The spraying distance was controlled to be 20 cm, the spraying pressure was 0.6 MPa, and after the spraying thickness reached 200 μm, it was dried in an oven at 80°C for 2 hours to obtain an organic white coating with low solar spectrum absorption rate that was resistant to ultraviolet radiation.
[0063] Example 4: The preparation method of the Y2O3@ZnO-200cycle-C coating in this example is carried out by the following steps:
[0064] Step 1. Preparation of Y2O3@ZnO-200cycle modified powder is as follows:
[0065] Directly transfer ZnO powder to the reaction chamber for coating and modification. Set the temperature of the reaction chamber to 250°C, the partial pressure of the precursor H2O and yttrium acetamidine to 5Pa, and alternately pass them into the chamber in pulse form. The source pulse time is 20s. Use high-purity nitrogen (99.999% volume purity) to purge the residual gas between pulses. The gas flow rate is 80ml / min, and the ALD cycle is set to 200 cycles. According to the above parameter settings, after the deposition is completed, take out the modified powder.
[0066] Step 2. Prepare white slurry:
[0067] Acrylic resin was selected as the organic binder, the pigment-to-base ratio was set to 1:3, the speed of the cutting mixer was set to 2000 rpm, and the mixture was stirred at room temperature for 2 h to obtain a white slurry.
[0068] Step 3. Spray the white slurry obtained in step 2 onto the alloy substrate:
[0069] Aluminum alloy was selected as the metal substrate. The aluminum alloy substrate after sandblasting was ultrasonically cleaned with acetone and anhydrous ethanol, and placed in the spraying room after drying. The spraying distance was controlled to be 10 cm, the spraying pressure was 0.8 MPa, and after the spraying thickness reached 200 μm, it was dried in an oven at 80°C for 2 hours to obtain an organic white coating with low solar spectrum absorption rate that was resistant to ultraviolet radiation.
[0070] For the coating prepared in the above embodiment, the following tests were performed:
[0071] XPS test: We used the Y2O3@ZnO-200cycle-A prepared in Example 1 to perform XPS test. The test results are as follows: Figure 1 As shown. The peaks of the 3d orbital of Y, with the 3d orbital double peak in the middle that is definitely yttrium oxide, show a positive shift of 0.2 to 0.5 eV. On the one hand, it may be that the surface containing Y reacts with the environmental moisture to form Y-OH sites. These Y-OH bonds are affected by the CO2 reaction to form YOC sites. On the other hand, due to the difference in electronegativity between Zn and Y, the electronegativity of Zn is greater than that of Y, and part of Y and Zn undergo charge shift to form Y-Zn bonds. These two aspects together lead to the shift of the 3d orbital of Y. The existence of the Y-Zn bond can adjust the electronic transition behavior of ZnO after ultraviolet irradiation, thereby achieving the protection of the white thermal control coating.
[0072] Solar spectrum absorption test: We used the Y2O3@ZnO-200cycle-A coating prepared in Example 1 to test the absorption of sunlight. The test showed that the Y2O3@ZnO-200cycle-A coating has good reflective performance in the solar spectrum band, with an average absorption rate of 12.37, which has reached the reflective performance of commercial coatings in the solar spectrum band.
[0073] Infrared emission measurement: We used the Y2O3@ZnO-200cycle-A coating prepared in Example 1 to test the absorption of sunlight. The test showed that the Y2O3@ZnO-200cycle-A coating has good spectral emission performance with an average reflectivity of 85.09, which has reached the infrared emission performance of commercial coatings.
[0074] Ultraviolet test: The Y2O3@ZnO-200cycle-A white coating prepared in Example 1 was subjected to ultraviolet irradiation test using a space ultraviolet irradiation simulation device. The thermal control performance test data of the white coating before and after ultraviolet irradiation were tested (e.g. Figure 4The comparison before and after irradiation shows that the Y2O3@ZnO-200cycle-A coating turns yellow after UV irradiation test, but the coating does not fall off or show the bottom, which means that the pigment modified by Y2O3 can protect the coating to a certain extent, so that the white coating after irradiation still maintains a certain thermal control performance and has UV resistance.
[0075] Mass loss test: After the UV irradiation test, the mass loss of the Y2O3@ZnO-200cycle-A white coating prepared in Example 1 before and after irradiation was measured using a high-precision balance. From the mass loss rate value, the mass loss rate of the coating under UV irradiation is extremely small, and its maximum loss rate is only 0.038%; as the UV irradiation time increases, the mass loss of the white coating first increases and then tends to be flat, and the mass loss rate increases rapidly in the initial stage of irradiation. After irradiation for 3500ESH, the mass loss rate of the coating remains basically unchanged.
[0076] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essential content of the present invention.
Claims
1. A method for preparing an organic white coating material with ultraviolet radiation resistance and low solar spectrum absorptivity, characterized in that: The following steps are involved: Step 1, preparing rare earth oxide modified ZnO pigment powder by ALD; Step 2: then mix evenly with an organic binder to obtain a white slurry; Step 3, spraying the white slurry on the substrate and drying it to obtain the coating; Wherein, in step 1, the rare earth oxide is Y2O3, CeO2 or La2O 3; ALD process parameters in step 1: inert fluidizing gas flow rate is 40ml / min-120ml / min, chamber temperature is 200℃-300℃, precursor pulse time is 5s-25s, purge gas cleaning time is 10s-30s, and deposition cycle number is 100-300cycles.
2. The method according to claim 1, characterized in that: The precursor of Y2O3 is yttrium acetoamidinate, the precursor of La2O3 is methylcyclopentadienyl lanthanum, and the precursor of CeO2 is cyclopentadienyl cerium.
3. The method according to claim 1, characterized in that: In step 2, the organic adhesive is epoxy resin, acrylic resin, silicone or polyethylene.
4. The method according to claim 1, characterized in that: In step 2, the mass ratio of the white slurry to the organic binder is 1:(1-5).
5. The method according to claim 1, characterized in that: In step 2, mix using a cutting mixer.
6. The method according to claim 4, characterized in that: The stirring rate is 1000rpm-3000rpm, and the stirring time is 1h-3h.
7. The method according to claim 1, characterized in that: In step 3, the substrate is an aluminum alloy, a titanium alloy, or a magnesium alloy.
8. The method according to claim 1, characterized in that: In step 3, the spraying distance is 10cm-30cm, and the spraying pressure is 0.4Mpa-1MPa.
9. A coating prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method for oxide ceramic coating on surface of wave-absorbing material powder
CN106399968A
Low Emissivity Glass Incorporating Phosphorescent Rare Earth Compounds
US20150291812A1